Pengaruh Media Sosial terhadap Wisatawan dalam Memilih Destinasi Wisata Kuliner di Dipatiukur Kota Bandung - Saskia Putri Aprilia; Fathur Rizky Pratama (Tamasya : Jurnal Pariwisata Indonesia, 2025)
This research aims to analyze the influence of social media on tourists' decisions in choosing a culinary tourist destination on Jl. Dipatiukur, Bandung City. In the current digital era, social media has become the main source of information for tourists who are looking for culinary recommendations. The research method used is qualitative with in-depth interviews and content analysis from social media platforms such as Instagram and TikTok. Research results show that interesting visual content, positive reviews, and active interaction between users and culinary business owners play an important role in shaping the perception of tourists. Social media not only increases the visibility of culinary destinations, but also builds trust and personal relationships between consumers and service providers. This finding provides strategic insight for culinary business owners in designing effective marketing campaigns through social media, as well as highlighting the importance of the role of social media in increasing the attractiveness of culinary tourism destinations in Bandung.